Genomic characterization of SARS-CoV-2 identified in a reemerging COVID-19 outbreak in Beijing's Xinfadi market in 2020 - Yong Zhang; Yang Pan; Xiang Zhao; Weifeng Shi; Zhixiao Chen; Sheng Zhang; Peipei Liu; Jinbo Xiao; Wenjie Tan; Dayan Wang; William J. Liu; Wenbo Xu; et al. (Elsevier, 2020)
After 56 days without coronavirus disease 2019 (COVID-19) cases, reemergent cases were reported in Beijing, China on June 11, 2020. Here, we report the genetic characteristics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) sequenced from the clinical specimens of 4 human cases and 2 environmental samples. The nucleotide similarity among six SARS-CoV-2 genomes ranged from 99.98% to 99.99%. Compared with the reference strain of SARS-CoV-2 (GenBank No. NC_045512), all six genome sequences shared the same substitutions at nt241 (C → T), nt3037 (C → T), nt14408 (C → T), nt23403 (A → G), nt28881 (G → A), nt28882 (G → A), and nt28883 (G → C), which are the characteristic nucleotide substitutions of L-lineage European branch I. This was also proved by the maximum likelihood phylogenetic tree based on the full-length genome of SARS-CoV-2. They also have a unique shared nucleotide substitution, nt6026 (C → T), which is the characteristic nucleotide substitution of SARS-CoV-2 in Beijing's Xinfadi outbreak. It is noteworthy that there is an amino acid D614G mutation caused by nt23403 substitution in all six genomes, which may enhance the virus's infectivity in humans and help it become the leading strain of the virus to spread around the world today. It is necessary to continuously monitor the genetic variation of SARS-CoV-2, focusing on the influence of key mutation sites of SARS-CoV-2 on viral transmission, clinical manifestations, severity, and course of disease.